Strategy of politeness through Japanese respect in the anime My Next Life as a Villainess: All Routes Lead to Doom Season 1 - Demiyati, Lely; Susanti, Rita; Aziz, Hafizh Abdul (Japanese Research on Linguistics, Literature, and Culture, 2023)
Japan is famous for its politeness in language. Politeness in Japanese is inseparable from culture. Anime is a form of global culture. Anime is also well-known as one of the reasons Japanese language learners are interested in Japanese. It is this background that makes the writer research "Strategy of Politeness through Japanese Respect in the Anime My Next Life as a Villainess: All Routes Lead to Doom Season 1". This data source is used because there are many uses of Japanese language honorifics in the conversations of the nobility. Honorifics found in data are analyzed using Yule's speech act theory (1996), Brown and Levinson's politeness strategies (1987), and Kabaya's Japanese language honorifics theory (2008). Based on the analysis results, many on-record strategies with positive politeness were found due to the status of the speech participants from among the nobility, who are used to various forms of respect. The don't do the FTA strategy was not found because the participants said their intentions clearly. The most widely used form of respect is sonkeigo because it respects the speech partner, and there is a difference in status. Factors in the use of honorifics that influence the use of sonkeigo and kenjougo are human relations, feelings and forms of delivery.